Characteristics and survival impact of polymorphonuclear leucocyte‐predominant malignant pleural effusions secondary to lung cancer. (18th June 2020) - Lee, Jaehee; Lee, Yong Hoon; Seo, Hyewon; Do, Young Woo; Lee, Deok Heon; Lee, Sang Yub; Lim, Jae Kwang; Yoo, Seung Soo; Lee, Shin Yup; Cha, Seung Ick; Park, Jae Yong; Kim, Chang Ho
Abstract: Introduction: In comparison with mononuclear leucocyte (MNL)‐predominant malignant pleural effusions (MPEs), polymorphonuclear leucocyte (PMNL)‐predominant MPEs have rarely been investigated and may be associated with a poorer prognosis. Objectives: To investigate the characteristics and survival impact of PMNL‐predominant MPEs secondary to lung cancer. Methods: This retrospective study included patients with MPE secondary to lung cancer, which were classified into the PMNL‐ and MNL‐predominant groups according to cellular predominance in the pleural fluid. Clinical, hematological, radiological, and pleural fluid data were compared between the groups, and the survival impact of PMNL predominance in MPE was evaluated. Results: Of the 193 MPEs included, 37 (19%) were characterised by PMNL predominance. Compared to the MNL‐predominant group, the PMNL‐predominant group showed significantly poorer patient performances ( P  = .001), higher white blood cell counts ( P  = .009), higher neutrophil counts, higher blood neutrophil‐to‐lymphocyte ratio ( P  = .046), higher serum C‐reactive protein ( P  = .003), lower serum albumin ( P  < .001), lower pleural fluid pH ( P  = .002) and higher pleural fluid lactate dehydrogenase ( P  = .029) levels. In contrast, most clinical and radiological findings, including the duration of symptoms, showed no significant intergroup differences. A shift towards MNL predominance was observed in only 38% of the PMNL‐predominant patients who underwent repeat thoracentesis. Overall survival of the PMNL‐predominant group was significantly shorter than the MNL‐predominant group ( P  = .003). Conclusions: PMNL predominance in MPEs secondary to lung cancer may be observed in variable phases with respect to the duration of symptoms and the time of thoracentesis. Overall, PMNL‐predominant MPEs were associated with more advanced stages and poorer survival outcomes, compared to MNL‐predominant MPEs.